2021
DOI: 10.1264/jsme2.me20136
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization and Distribution of Agar-degrading <i>Steroidobacter agaridevorans</i> sp. nov., Isolated from Rhizosphere Soils

Abstract: The environment of plant rhizosphere soil differs from that of non-rhizosphere soil due to the secretion of mucilage polysaccharides from the roots. This environment is regarded as one of the preferential habitats for agar-degrading bacteria. In a previous study, agar-degrading Steroidobacter agariperforans KA5-B T was isolated from agar-enriched agricultural soil using diffusible metabolites from Rhizobiales bacteria. Based on the hypothesis that similar characteristic bacteria still exist in the rhizosphere,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
7
1
Order By: Relevance
“…S3c–f). This phenomenon was not consistent with previous studies [2, 6], showing that two isolates of the genus Steroidobacter displayed remarkably improved growth when cultivated with the metabolites produced by bacteria belonging to the order Rhizobiales . This suggested that strain S1-65 T survived in co-evolved microbial communities with structures distinct from where those two isolates were isolated, leading to different microbial interaction patterns.…”
Section: Detection Of Social Interactionscontrasting
confidence: 99%
See 4 more Smart Citations
“…S3c–f). This phenomenon was not consistent with previous studies [2, 6], showing that two isolates of the genus Steroidobacter displayed remarkably improved growth when cultivated with the metabolites produced by bacteria belonging to the order Rhizobiales . This suggested that strain S1-65 T survived in co-evolved microbial communities with structures distinct from where those two isolates were isolated, leading to different microbial interaction patterns.…”
Section: Detection Of Social Interactionscontrasting
confidence: 99%
“…ISP9 supplemented with 1 % glucose served as a positive control. Polysaccharide degradation capabilities were tested following the method described by Ikenaga et al [6]. Other physiological and biochemical properties of strains S1-65 T and KA5-B T were further tested using the API 20 NE systems (bioMérieux), according to the manufacturer’s instructions.…”
Section: Morphology and Physiologymentioning
confidence: 99%
See 3 more Smart Citations